Association of Serum Uric Acid, Urea Nitrogen, and Urine Specific Gravity Levels at 16–18 Weeks of Gestation with the Risk of Gestational Diabetes Mellitus - Li Y; Yu T; Liu Z; Chen H; Liu Y; Wei Y; Sun R; Zhang H; Wang W; Lu Y; Zhou Y; Deng G; et al. (Diabetes, Metabolic Syndrome and Obesity, 2020)
Yan Li,1,* Tingwei Yu,2,* Zengyou Liu,2 Hengying Chen,3 Yao Liu,4 Yuanhuan Wei,4 Ruifang Sun,4 Hongmei Zhang,2 Wei Wang,2 Yihua Lu,2 Yingyu Zhou,1 Guifang Deng,4 Zheqing Zhang1 1Department of Nutrition and Food Hygiene, Guangdong Provincial Key Laboratory of Tropical Disease Research, School of Public Health, Southern Medical University, Guangzhou, People’s Republic of China; 2Department of Obstetrics, Union Shenzhen Hospital of Huazhong University of Science and Technology, Shenzhen, People’s Republic of China; 3Injury Prevention Research Center, Shantou University Medical College, Shantou, People’s Republic of China; 4Department of Clinical Nutrition, Union Shenzhen Hospital of Huazhong University of Science and Technology, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zheqing ZhangDepartment of Nutrition and Food Hygiene, Guangdong Provincial Key Laboratory of Tropical Disease Research, School of Public Health, Southern Medical University, No. 1023-1063, Shatai South Road, Baiyun District, Guangzhou, Guangdong 510515, People’s Republic of ChinaEmail zzqaa501@smu.edu.cnGuifang DengDepartment of Clinical Nutrition, Union Shenzhen Hospital of Huazhong University of Science and Technology, No. 89 Taoyuan Road, Shenzhen, Guangdong 518052, People’s Republic of ChinaEmail misyfly@163.comObjective: To evaluate the associations of serum uric acid (UA), urea nitrogen (UN), and urine specific gravity (USG) levels in the first trimester of pregnancy with the risk of gestational diabetes mellitus (GDM).Patients and Methods: A retrospective cohort study was conducted in 1,769 pregnant women aged 31.55 ± 3.91 years. UA, UN, and USG levels were measured during the 16– 18th week of gestation. GDM was diagnosed by an oral 75 g glucose tolerance test during the 24– 28th week of gestation.Results: A multivariate adjusted logistic regression analysis showed that UA levels in the highest quartile increased the risk of GDM by 55.7% (odds ratio [OR]: 1.557, 95% confidence interval [CI]: 1.055– 2.298; p = 0.026) compared to those in the lowest quartile. USG levels in the second, third, and fourth quartiles increased the risk of GDM by 67.6% (95% CI: 1.090– 2.421), 112.4% (95% CI: 1.446– 3.119), and 94.5% (95% CI: 1.314– 2.880), respectively, compared to those in the first quartile (p trend = 0.001). No significant association between UN levels and the GDM risk was observed. When the extreme composite biomarker score quartiles were compared, the adjusted OR (95% CI) for GDM was 1.909 (95% CI: 1.332– 2.736). Age-stratified analyses revealed similar results in women aged ≤ 35 years only, but not in those aged > 35 years.Conclusion: Higher levels of UA and USG and a higher composite kidney function biomarker score during the 16– 18th week of gestation were positively and independently associated with an increased risk of GDM.Keywords: uric acid, urea nitrogen, urine specific gravity, gestational diabetes mellitus, retrospective cohort study